Analisis Kepuasan Pasien Terhadap Pelayanan Kesehatan di RSUD Lahat Tahun 2021 - Beti Hariani; Arie Wahyudi; Hamyatri Rawalilah (Jurnal Kesehatan Saelmakers PERDANA, 2022)
Satisfaction is the response or level of feeling of the patient obtained after the patient receives a health service product by comparing the perceived performance or result with the patient's needs and expectations. This study aims to analyze patient satisfaction with health services at Lahat Hospital in 2021. This study was a quantitative study with a cross sectional approach. The sampling technique used stratified random sampling obtained a sample of 97 respondents. Data was collected using a questionnaire, then the data was analyzed using the chi square test with a significance level of p value <0.05. The data were also analyzed using logistic regression test to determine the dominant variables that affect patient satisfaction. The results of the Community Satisfaction Index (IKM) in the Outpatient Lahat Hospital in 2021 were 77.44 with a service quality of "B" and service performance "Good. The results of bivariate analysis showed that there was a relationship between service requirements and patient satisfaction (p=0.005), service procedures (p=0.000), service completion time (p=0.001). service fee (p=0.005), specification of service type (p=0.006), competence of service implementer (p=0.011), behavior of service provider (p=0.000), handling of complaints, suggestions and inputs, facilities and infrastructure (p=0.000). The results of multivariate analysis with logistic regression test showed that the most dominant variable was facilities and infrastructure (p=0.041) p value <0.05 with the largest OR value of 383.398. It is recommended to hospitals to further improve facilities and infrastructure so that patient satisfaction can increase